Household food insecurity associated with gestacional and neonatal outcomes: a systematic review - Ana Lucia Pires Augusto; Aléxia Vieira de Abreu Rodrigues; Talita Barbosa Domingos; Rosana Salles-Costa (BMC, 2020)
Abstract Background Food insecurity (FI) occurs when people lack secure access to sufficient amounts of safe and nutritious food. FI has been associated with negative effects on human health, including during the prenatal and neonatal periods. The objective of this study is to evaluate the consequences of FI for pregnant women's and newborns' health. Methods A literature search was performed with three independent researchers based on the PRISMA guidelines; the search covered the period of November 2008 to July 2019 and was conducted in the following databases: the US National Library of Medicine at the National Institutes of Health (PubMed), Latin American and Caribbean Health Sciences (LILACS), Cochrane Library, Web of Science, Embase, Scopus and OpenGrey. The terms and descriptors were defined by consulting the Medical Subject Headings (MeSH) and Health Sciences Descriptors (DeCS) platforms and mainly included "food security", "food insecurity", "pregnancy" and "newborn". The studies were selected through a title and abstract review and then a reading of the full text. The quality of the studies and the risk of bias were analysed based on the criteria defined in the "Joanna Briggs Institute Reviewers' Manual" and by Guyatt and colleagues for interventional studies. The population, study design, FI measurement instruments, FI proportions, outcomes, confounders and results were extracted from the 37 studies that were selected according to the eligibility and quality criteria. Results FI ​​proportions ranged from 5.2 to 87%. Most studies were conducted with African populations (42.2%) and applied globally used scales to assess FI (56.7%); 27% of the studies adapted scales. There were wide variations in the instruments used to estimate FI. The main outcomes related to FI included stress, anxiety and depression during pregnancy, followed by dietary quality and dietary diversity. Associations of FI with birth defects, neonatal mortality and the early introduction of animal milk to the infant's diet were also observed. Conclusions It is necessary to pay attention to the diversity of FI measurement instruments before FI results are compared. FI can be a risk factor for depression and stress during pregnancy, as well as for neonatal mortality, newborn health problems and breastfeeding interruption. Trial registration This systematic review was registered on PROSPERO ( CRD42018109478 ).